Moderasi Agama dalam Masyarakat Multikulturaldalam Bingkai Kekristenan di Indonesia - Situmorang, Alexander (CHARISTHEO: Jurnal Teologi dan Pendidikan Agama Kristen, 2025)
Indonesia is a country with a multicultural society rich in ethnic, cultural and religious diversity. As a country with diversity, there are certainly challenges faced in maintaining harmony and tolerance among religious communities. Therefore, religious moderation is key in the effort to create a peaceful and harmonious life in the midst of existing differences. This study aims to analyze the role of religious moderation in the context of Christianity in Indonesia, focusing on how the values of moderation are internalized and implemented by Christians in interacting with a pluralistic society. In this research, a qualitative-literature study methodology is used. Data were obtained from written sources, such as books, journals, articles and other documents. This is done to explore the meanings, patterns, and perspectives contained in the existing literature. The results showed that religious moderation has a significant role in shaping the attitudes and behavior of Christians in Indonesia. Values such as tolerance, mutual respect, and interfaith cooperation become an important foundation in social interactions in which Christians in Indonesia are involved in various activities in Indonesia.